2010
DOI: 10.15288/jsad.2010.71.313
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Etiology of Associations Between Perceived Parenting and Adolescents' Alcohol Use: Common Genetic and/or Environmental Liabilities?

Abstract: ABSTRACT. Objective: Although twin studies yield consistent evidence of heritability in the frequency of adolescent alcohol use, parallel findings on parenting are more equivocal, supporting the role of genes in affective parenting but not as supportive in relation to parental control. The extent to which these patterns generalize to more nuanced forms of parenting is less clear. Furthermore, despite evidence linking parents' socialization practices with adolescents' alcohol-use behaviors, this study is the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Adolescence represents a period of unique vulnerability for developing addiction (4) , with both parents and peers acting as role models and contributing to risk or resilience (5,36,37) . It is a challenge in observational epidemiology to distinguish the effect of an exposure such as dietary preference in childhood from covarying influences such as parenting style or socio-economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence represents a period of unique vulnerability for developing addiction (4) , with both parents and peers acting as role models and contributing to risk or resilience (5,36,37) . It is a challenge in observational epidemiology to distinguish the effect of an exposure such as dietary preference in childhood from covarying influences such as parenting style or socio-economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined different aspects of family socialization or similar aspects under different terms such as cohesion, overprotection, care, warmth, autonomy granting, etc. (e.g., Barnes et al, 2006;Creemers et al, 2011;Jiménez-Iglesias, Moreno, Granado-Alcón, & López, 2012;Latendresse et al, 2010), and have found that those aspects of parenting are significantly associated with adolescent substance use.…”
Section: Parenting Styles and Polysubstance Usementioning
confidence: 99%
“…Mothers' care-giving behaviour and/or "mothering" are often considered as "parenting" behaviour as a whole (Hair et al, 2008;Latendresse et al, 2010). Additionally, most studies examining parenting styles and influences examine these variables with mothers and fathers lumped together with the word "parents" at the item level (e.g., Barnes et al, 2006;Patock-Peckham et al, 2011).…”
Section: Challenges (Gaps) In the Current Parenting-psu Studiesmentioning
confidence: 99%
“…It has also been associated with less anxiety in preadolescents (9-14 year-olds), than are authoritarian or permissive styles. It has also been associated with lower levels of alcohol and drug use (193)(194)(195)(196).…”
Section: Parenting Practicesmentioning
confidence: 99%
“…It has also been associated with less anxiety in preadolescents (9-14 year-olds), than are authoritarian or permissive styles. It has also been associated with lower levels of alcohol and drug use (193)(194)(195)(196).The setting of boundaries and expectations for acceptable behaviour ("norming") is a central parenting practice. Inconsistent or unclear behaviour limits and parental 24 permissiveness have been strongly associated with substance use and delinquency (161) and externalising behaviour as discussed above (158).…”
mentioning
confidence: 99%